Digitalisation of Design Research - A case study to illustrate the use of digital technologies and tools for collaboration in Design Research projects - Gerholz, Karl-Heinz [Verfasser]; Ciolek, Sebastian [Verfasser]; Wagner, Anne [Verfasser] (My University, 2020)
"The cooperation between research and practice is a constitutive element of Design-based Research (DBR). Despite its importance, the process and the challenges of cooperation between these fields are not well studied to date. This paper aims to establish a better understanding of how cooperation among researchers and practitioners can be managed and how cooperation is related to the design and implementation of innovations. For this purpose, we draw on a DBR project as an example, wherein the European model of validation was adapted to the field of geriatric care in Germany. We discuss insights into objectives, abilities, attitudes and restrictions of the cooperating parties in this example DBR project. We demonstrate how cooperation can help to overcome some of the obstacles in the process of developing innovation in the field. However, we additionally critically examine how cooperation between research and practice can be managed and ignite innovation that over time may have a transformative effect on practices often taken for granted in education. On this basis, we conclude that cooperation promotes mutual learning by both researchers and practitioners." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; G 2.2.1 Technologisierung; L 4.1.2 Elektronische Medien; Berufsbildungsforschung; Gestaltungsbasierte Forschung; Forschungskooperation; Theorie-Praxis; Digitalisierung; Digitale Medien